IL-10 regulates Th17 response to inhibit hepatobiliary injury caused by Clonorchis sinensis infection in C57BL/6J mice - Zhang, Beibei; Wang, Jianling; Liu, Man; Zhao, Qianqian; Yu, Guozhi; Zhang, Bo; Hua, Hui; Xu, Jinyao; Li, Jing; Yu, Qian; Koda, Stephane; Xu, Yin-Hai; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Clonorchiasis caused by Clonorchis sinensis is a mainly foodborne parasitic disease. It can lead to hepatobiliary duct inflammation, fibrosis, obstructive jaundice, liver cirrhosis, and even cholangiocarcinoma. Interleukin (IL)-10 is an immune-regulatory cytokine, which plays an immunosuppressive role during infection. Our previous study found that IL-10 was increased in mice with C. sinensis infection. However, the role and mechanism of IL-10 playing in hepatobiliary injury induced by C. sinensis infection remain unknown. Herein, Il10+/+ mice and Il10+/- mice were used to be infected with C. sinensis. It was found that IL-10 deficiency aggravated biliary hyperplasia and exacerbated periductal fibrosis induced by C. sinensis infection. Moreover, IL-10 deficiency increased CD4+T cells and CD8+T cells but not macrophages in the liver of mice with infection. There were no obvious differences in Th1 and Treg cells between Il10+/+and Il10+/- mice infected with C. sinensis. However, the proportion of Th17 cells in CD4+T cells in Il10+/- infected mice was significantly higher than that in Il10+/+ infected mice. IL-10 deficiency also enhanced the increase of Th17 cells induced by ESPs stimulation in vitro. Taken together, our results suggest that IL-10 plays a protective role in hepatobiliary injury induced by C. sinensis infection via inhibiting Th17 cells, which could deepen our understanding of the immunopathology of clonorchiasis.